A comparative study on applying functional therapeutic method versus class II elastics edgewise in class II skeletal patients - Eslamian L (Tehran University of Medical Sciences, 2002)
Various comparative studies have been conducted to investigate the effect of functional and fixed appliances in treatment of class II skeletal disorders. The aim of this study was to compare Bionator and Edgewise appliances associated with class II elastics in the treatment of class II skeletal patients, without extraction. Lateral cephalograms of 30 patients (16 girls, 14 boys), 10-13 years old, with class II div I maolocclusion, treated with Bionater and Edgewise appliances were investigated before and after treatment. SNA, SNB, ANB, " to SN, IMP A, mandibular and maxillary lengths, upper anterior facial height to lower anterior facial height, overjet and overbite were measured in each group before and after treatment. The results were analyzed by paired t- test. The magnification of linear measurements were calculated. The differences between variables in 2 groups were compared by t-test. There was no significant difference, regarding age and sex. In both groups, increase in SNB, mandibular length, and IMPA and decrease in " to SN, overjet and overbite and upper anterior face height to lower anterior face height after treatment were statistically significant. Comparing 2 groups before and after treatment showed that increase in SNB and decrease of ANB, overjet and overbite were more in Bionator group than fixed group, which were significant. Decrease in upper anterior face height to lower anterior face height, and increase in IMPA and mandibular length were more in Bionater group but the differences were not statistically significant.